Evaluasi Ketaatan Penggunaan Antihipertensi di Apotek X _ Yogyakarta Periode Tahun 2009 Berdasarkan Parameter Medication Possession Ratio - RITA SUHADI (Fakultas Farmasi Universitas Pancasila, 2011)
World Health Organization reported that hypertension was in the top rank as global causes of death in 2009. Adherence to the antihypertensive medication reduced risks of various cardiovascular diseases. A cross-sectional study has been carried out to observe profile of the use of antihypertensive and to evaluate patient’s compliance based on Medication Possession Ratio (MPR) at X-Pharmacy Yogyakarta in 2009. Study subjects were the prescription of antihypertensive for patient regularly visits at least 3 times. The MPR was calculated as the ratio of the sum of the days supply of the prescription filled, excluding the latest prescription, divided by number of days filled. Results showed that the class and type of the most commonly prescribed antihypertensives based on the number of units and the highest mean units per prescription was the ACEI (captopril 25mg) and based on the frequency of prescribing was CCB (amlodipin 5mg). The use of generic drugs versus branded medicines 5.6 times in the units, 3.2 times more in the frequency of prescribing, and 1.7 times more generic drugs in mean units per prescription. There was no significant difference between the adherence of patients based on sex, with or without costsharing; as well as single or combination antihypertensive based on MPR (p > 0.05); mean MPR was 0.78 ± 0.15 (range 0.41-1.00); and as many as 50.00 0 had MPR > 0.8 and considered as adherent patients.